Care in the Last Year of Life for Community Patients With Heart Failure. (May 2015) - Dunlay, Shannon M.; Redfield, Margaret M.; Jiang, Ruoxiang; Weston, Susan A.; Roger, Véronique L.
<x xml:space="preserve">Abstract</x> Background— Healthcare utilization peaks at the end of life (EOL) in patients with heart failure. However, it is unclear what factors affect end of life utilization in patients with heart failure and if utilization has changed over time. Methods and Results— Southeastern Minnesota residents with heart failure were prospectively enrolled into a longitudinal cohort study from 2003 to 2011. Patients who died before December 31, 2012, were included in the analysis. Information on hospitalizations and outpatient visits in the last year of life was obtained using administrative sources. Negative binomial regression was used to assess the association between patient characteristics and utilization. The 698 decedents (47.3% men; 53.4% preserved ejection fraction) experienced 1528 hospitalizations (median 2 per person; range, 0–12; 37.6% because of cardiovascular causes) and 12 927 outpatient visits (median 14 per person; range, 0–119) in their last year of life. Most patients (81.5%) were hospitalized at least once and 28.4% died in the hospital. Patients who were older and those with dementia had lower utilization. Patients who were married, resided in a skilled nursing facility, and had more comorbidities had higher utilization. Patients with preserved ejection fraction had higher rates of noncardiovascular hospitalizations although other utilization was similar. Over time, rates of hospitalizations and outpatient visits decreased, whereas palliative care consults and enrollment in hospice increased. Conclusions— Although patient factors remain associated with differential healthcare utilization at the end of life, utilization declined over time and use of palliative care services increased. These results are encouraging given the high resource use in patients with heart failure.